MODELING OF THE SWITCHING DC VOLTAGE STABILIZER BASED ON HIGH-FREQUENCY MAGNETIC AMPLIFIERS - YASKIV, VOLODYMYR; DOMNIN, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents mathematical modeling of the operating modes of a switching DC voltage stabilizer based on high-frequency magnetic amplifiers. The relevance of conducting such research is substantiated.The purpose of the research is to build a mathematical model of the control circuit of a high-frequency magnetic amplifier in a switching DC voltage stabilizer based on high-frequency magnetic amplifiers, to model such a converter as a whole, and to use the results of mathematical modeling in computer simulation of such power converters in order to obtain their frequency characteristics and to investigate the conditions for ensuring their stable operation.To achieve this purpose, the following tasks were resolved: the principle of operation of the power converter based on an analysis of its power circuit in a push-pull configuration was examined; the principle of operation of the control circuits of the high-frequency magnetic amplifier was explained; the choice of the control circuit for its mathematical modeling was justified; mathematical modeling of the control circuit of the high-frequency magnetic amplifier and of the switching DC voltage stabilizer as a whole was conducted. Based on the results of the mathematical modeling of the converter, its computer simulation was performed, frequency characteristics were built, and the conditions for ensuring stable operation of the switching DC voltage stabilizer based on high-frequency magnetic amplifiers were formulated. Taking these conditions into account, appropriate compensating circuits were developed, and corrected frequency characteristics of the regulator based on high-frequency magnetic amplifiers were obtained.Mathematical and computer modeling of the proposed methods was carried out, in particular a mathematical model of the regulator based on a high-frequency magnetic amplifier was developed, and its frequency-domain analysis was performed using the PSPICE software package.
Keywords: switching DC voltage stabilizer; high-frequency magnetic amplifier; rectangular hysteresis loop; control circuit; simulation; frequency characteristics